STRATEGI PEMASARAN DALAM UPAYA MENARIK MINAT NASABAH MENGGUNAKAN PRODUK TABUNGAN SIGINJAI MUDHARABAH PADA BANK JAMBI SYARIAH - Murni Putri Pertiwi Silalahi; Eja Armaz Hardi; Eri Nofriza (Pusat Riset dan Inovasi Nasional, 2023)
Islamic banks are financial institutions that are principled in Islamic law. All activities carried out must also be in accordance with the Qur'an and Sunnah. The increasing number of banking institutions in Indonesia will lead to competition between banks. Therefore, to win this competition, bank companies must be able to fulfill a customer satisfaction. This study aims to determine the marketing strategy in an effort to attract customers to use the siginjai mudharabah savings product at Bank Jambi Syariah KC Simpang IV Sipin. In this study using qualitative methods. In this case the researcher intends to provide a description of the marketing strategy for the Siginjai mudharabah savings product and the constraints in marketing the product. The data source used is the primary data source which is directly obtained from the main source. Data collection techniques used are interviews and documentation. Data analysis techniques with inductive patterns that are based on facts that are specific to be studied, analyzed, and concluded so that they apply in general. The results of the research analysis show that Bank Jambi Syariah has carried out a 7p + Is marketing mix even though the implementation of the marketing strategy at Bank Jambi Syariah KC Simpang IV Sipin has not been implemented optimally, especially in the field of promotion. The lack of maximum performance in the field of promotion is due to the lack of promotion using social media. Even though social media has a very important role in introducing products to the wider community and there is still a limited number of offices in each city which makes it difficult for customers to access Bank Jambi Syariah.